Aid or exploitation?: Food-for-work, cash-for-work, and the production of “beneficiary-workers” in Ethiopia and Haiti - Carruth, Lauren; Freeman, Scott (World development, 2021)
•Many beneficiaries must perform manual labor to qualify for food or cash aid.•These beneficiary-workers are neither passive recipients of charity, nor employees.•Beneficiary-workers are the lowest-paid, least powerful workers in the aid industry.•As such, beneficiary-workers are alienated from the means of producing aid programs.•Food- and cash-for-work are designed primarily to improve work ethic of the poor. The distinct subject positions of “beneficiaries” and “aid workers” pervade global aid vernacular, the grey development literature, and the field of development studies, but this binary obscures additional and vital forms of labor within the global aid industry. This analysis is based on the juxtaposition, comparison, and historical contextualization of two case studies drawing on two independent ethnographic research projects in the Somali Region of Ethiopia and southwestern Haiti. We find that although not designated either “employees” or “aid workers,” many beneficiaries are required to work to qualify for assistance: for example, food-for-work programs in Ethiopia and cash-for-work programs in Haiti both require beneficiaries to perform difficult manual labor with aid agencies to qualify for disbursements of food or cash. Accordingly, participants in these programs figure themselves workers and not the passive recipients of charity, and in both places, we find that participants critique the inadequacy of the wages for their work. Beneficiaries who work for aid are therefore what we call “beneficiary-workers:” they work within the aid industry, but are neither officially employed nor adequately compensated for their labor. Further, these beneficiary-workers are alienated both from the benefits of their labor and the means of designing or leading the aid programs on which they depend. Aid that requires beneficiary-workers’ labor is therefore not fundamentally designed to alleviate poverty or spur economic development; it is instead designed to discipline the poor and to valorize and justify the aid organizations that delimit their labor. By revealing the effects of food-for-work and cash-for-work project in these two places, and by highlighting the critiques of work-for-aid projects leveled by participants themselves, this analysis questions the ethics and appropriateness of food-for-work and cash-for-work projects.